2022
DOI: 10.3389/fneur.2022.938655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Interleukin-8 and Serum Amyloid A With Anxiety Symptoms in Patients With Cerebral Small Vessel Disease

Abstract: ObjectiveCerebral small vessel disease (CSVD) is a clinical syndrome caused by pathological changes in small vessels. Anxiety is a common symptom of CSVD. Previous studies have reported the association between inflammatory factors and anxiety in other diseases, but this association in patients with CSVD remains uncovered. Our study aimed to investigate whether serum inflammatory factors correlated with anxiety in patients with CSVD.MethodsA total of 245 CSVD patients confirmed using brain magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recent literature in patients with cerebral microvascular disease has implicated increased SAA and CRP with a cluster of proinflammatory cytokines (IL-6, IL-8, IL-10, and TNF-a) in persistent anxiety. 52 SAA and CRP correlated strongly in our data set, but differed in the discriminability of TBI severity. Though the ubiquitous role of SAA in acute phase response makes it a more challenging therapeutic target, there is the potential for research into the neuroprotective blockade of molecules either up- or downstream to SAA in various pathways.…”
Section: Discussionmentioning
confidence: 57%
“…Recent literature in patients with cerebral microvascular disease has implicated increased SAA and CRP with a cluster of proinflammatory cytokines (IL-6, IL-8, IL-10, and TNF-a) in persistent anxiety. 52 SAA and CRP correlated strongly in our data set, but differed in the discriminability of TBI severity. Though the ubiquitous role of SAA in acute phase response makes it a more challenging therapeutic target, there is the potential for research into the neuroprotective blockade of molecules either up- or downstream to SAA in various pathways.…”
Section: Discussionmentioning
confidence: 57%
“…13 However, we found that there was no statistically significant relationship between ESR and symptoms of anxiety in psoriasis patients, which was consistent with previous work conducted in Cerebral Small Vessel Disease. 32 Taken together, these findings suggest a close relationship between CRP and ESR level and depression in psoriasis, which may encourage clinicians to screen for depression and to control inflammatory levels may relieve depression in psoriasis patients.…”
mentioning
confidence: 69%